Adaptation pathways to inform policy and practice in the context of development. Issue 140 (February 2023) - Sparkes, Edward; Totin, Edmond; Werners, Saskia E.; Wise, Russell M.; Butler, James R.A.; Vincent, Katharine
Abstract: Adaptation pathways are a decision-focused approach to account for future uncertainties and complexities in planning and implementation of adaptation actions. The pathways approach incorporates flexibility into decision making to accommodate for changing conditions over time, and to reduce undesirable path dependencies and maladaptive consequences. While the pathways approach for adaptation planning has received great interest from both climate scientists and practitioners, there has been little specific guidance on how to implement them and how to sustain the resulting outcomes. Accordingly, pathways approaches include diversified methodologies, with scope for reorienting and adjusting methods for different decision contexts. This special issue explores both theoretical and empirical cases of adaptation pathways in different contexts. A learning framework on adaptation pathways has been developed from a systematic review of adaptation literature. In this editorial, the framework is used to characterize the twelve case studies presented in the special issue, followed by a synthesis of lessons which point to some critical research gaps in adaptation pathways. Highlights: Pathways approaches have diversified methods for different decision contexts. Engaging stakeholders with different values, goals, and knowledge was well represented in the literature. Pathways development underestimates the complexity of path dependencies. Monitoring and evaluation approaches are underrepresented in pathways literature and practices. Using a learning framework accommodates structured analysis of pathways approaches.